A Study on the Translation of Culturally Unique Chinese Terms Based on Corpora — Taking English Translations of The Analects as an Example - Yan Shi; Weihua Hu (Journal of Linguistics and Communication Studies, 2024)
Culturally unique terms carry rich cultural connotations, and the uniqueness, diversity, and contemporaneity of these terms pose significant challenges for translation. The accuracy of translating culturally unique terms is closely related to the quality of the translation. Therefore, exploring appropriate translation strategies for translating culturally unique terms is a worthwhile topic of study. Based on a parallel corpus of Chinese and English translations of The Analects, this study utilizes adaptation theory to examine the translation strategies for the original concepts in Gu Hongming’s version of The Analects. Wei Yucun categorizes the unique cultural concepts in The Analects into three types: material culture, institutional customs, and spiritual culture. The study finds that there are a total of 1,072 original concepts in The Analects, including 120 from material culture, 516 from institutional customs, and 436 from spiritual culture, which correspond to the surface, middle, and inner layers of culture. The translation strategies for different categories of original concepts vary; thus, translators should actively adapt to the different contexts of the target culture’s surface, middle, and inner layers, employing corresponding translation strategies for each category of original concepts to further promote cultural integration between China and the West, construct a translation discourse system, and facilitate the dissemination of traditional Chinese culture abroad.